Simulation of a pilot‐scale dual‐fluidized‐bed gasifier for biomass. Issue 3 (3rd February 2014) - Liao, Chang‐hsien; Summers, Matthew; Seiser, Reinhard; Cattolica, Robert; Herz, Richard
<x xml:space="preserve">Abstract</x> A dual‐fluidized‐bed gasifier was constructed and operated at the Woodland Biomass Research Center in Woodland, CA. The pilot‐scale gasifier had a capacity of 5 tons/day of feedstock and was based on the Pyrox process developed by Kunii et al. In this system, the fluidized‐bed combustion process with air is separated from the biomass gasification process with steam and recycle gas. This decreases the nitrogen content in the producer gas. The heat released in the combustion of the char is transported by a ceramic bed material circulating between the combustor and gasifier. Commercial wood pellets were used as feedstock for the present study. Gas composition, temperatures, and pressures were measured to characterize the operation of the gasifier. A positive feature of the system was the high circulation rate and efficient energy transfer between the combustor and gasifier. Analysis of the system was performed using Aspen Plus™ software to calculate mass and energy‐balances. A restricted equilibrium model for the producer‐gas composition agreed reasonably well with the measured non‐equilibrium gas composition for most gases. The restricted equilibrium model over‐predicted the H2 concentrations. A more complex rate‐based kinetic model would be necessary to fully capture the details of the non‐equilibrium gas composition in this pilot‐scale gasifier. © 2014 American Institute of Chemical Engineers Environ Prog, 33: 732–736, 2014